Subtyping of phosphoglucomutase locus 1 (PGM1) polymorphism in some populations of Rwanda: description of variant phenotypes, "haplotype" frequencies, and linkage disequilibrium data. - Santachiara-Benerecetti, A S (1982)
Some populations of Rwanda (South Twa Pygmies, Hutu, and Tutsi) have been analyzed by acid starch gel electrophoresis for the subtyping of PGM1 polymorphism. The new polymorphic third PGM11 allele, the PGM1(1Twa), which we recently detected in Twa Pygmies from North Rwanda, has not been found in this survey, whereas the rare PGM1(6) allele attains subpolymorphic frequencies in all groups. Comparison between the various populations of Rwanda shows that they differ significantly from each other with the exception of South Twa Pygmies and Tutsi. A relatively low frequency (9.6%) of the PGM1(2S) allele appears to be typical of North Twa Pygmies; a low frequency of PGM1(2F) (1.2%-3.6%) has been found in all these groups but not in the Hutu (6.4%); and a particularly high incidence of the PGM1(1F) allele (the highest so far reported) has been observed in the South Twa Pygmies (20%) and in the Tutsi (18%). The PGM1(1Twa) and PGM1(6) enzymes, which in acid starch gel are not distinguishable, can be clearly differentiated by isoelectric focusing. In addition, the same technique has shown that the rare PGM1(7) allele observed in one Hutu is different from that found at polymorphic frequency in the Japanese and from a rare PGM1(7) allele found in Germany. On the very likely hypothesis that the PGM1(1S), PGM1(1F), PGM1(2S), and PGM1(2F) result from variations at two different polymorphic sites, 1/2 and F/S, within the PGM1 structural gene, all the available population data have been analyzed to investigate whether preferential combinations (haplotypes) were identifiable. Whereas Caucasians show a prevalence of 2F and 1S combination with an 8.02% mean value of linkage disequilibrium expressed as % Dmax, from the very few and scattered African data, it is impossible to draw any inference at present.